Evaluating User Experience (UX) of Virtual Reality for Sewang Dance - Wan Mohd Isa, Wan Abdul Rahim; Suhaimi, Ahmad Iqbal Hakim; Noordin, Nurulhuda; Roslan, Nuraina Anis; Azhar, Nur Hamizah; Hussain, Sulaini (Journal of Advanced Research Design, 2025)
Sewang Dance virtual reality (VR) is a virtual reality that showcases the dance traditions of the Orang Asli people. The objective of the research is to evaluate significant elements of user experience, including efficiency, stimulation, attractiveness, dependability, novelty, and perspicuity. The User Experience Questionnaire (UEQ) framework is used in this research together with the design of the survey questionnaire. The main research objectives are then developed once the data has been retrieved and examined using the User Experience Questionnaire (UEQ) Analysis framework, tool, and analysis. Data gathering from 384 respondents and the setting for the research in Selangor, Malaysia. Different design aspects and user experience (UX) concerns should be considered to boost the Sewang Dance VR in terms of efficiency, stimulation, attractiveness, dependability, novelty, and perspicuity. Future work may include such as one-on-one interviewing or focus groups, to further enhance the UX of the Sewang Dance VR.